Análise experimental de pilares de concreto armado reforçados empregando diferentes técnicas de confinamento - SILVA, Ana Paula Romeira (2022)
Every year there are new techniques used for the fortification and restoration of structures in reinforced concrete, especially the ones applied for reinforcing columns, aiming confinement and raise of the bearing capacity of the same. Given this context, this research conducted an experimental analysis about the different reinforcement techniques used in reinforced concrete columns. Purposing to evaluate the confinement efficiency, an event which consists in restricting the lateral expansion through the jacketing of columns, the behavior of the variation of the cross section, the bearing capacity, ways of breaks and deformations. The tested series consisted of 10 columns subjected to centered axial compression. 500 mm long with columns were cast, using circular and square sections for each of the situations, respectively. As such, two columns were cast as reference with diameter of 150 mm and base (140 x 140) mm, two strengthened columns with reinforced concrete with diameter of 220 mm and base (220 x 220) mm, two using reinforced mortar with welded screen and diameter of 200 mm and base (190 x 190) mm, two using reinforced mortar with fiberglass screen, dimensions equal to the welded screen and two using a system composed of carbon fiber with diameter of 150 mm and the base (140 x 140) mm. The results indicated that the circular section columns showed a superior performance when compared to the ones of the square section. When analyzing the efficiency of the reinforcements, the columns of reinforced concrete, carbon fiber and welded screen, showed up with a significant increase in bearing capacity. The columns with circular cross section achieved values greater than 170% in relation to the reference ones, probably because the confinement reaction is uniformly distributed, unlike the square section columns, where stress concentration occurs by the effect of bending. Among the sections of square columns, the column reinforced with carbon fiber is more efficient, showing up strength gain exceeding 80% compared to the reference column.